Artificial neural networks and machine learning -- ICANN 2019 : workshop and special sessions : 28th International Conference on Artificial Neural Networks, Munich, Germany, September 17-19, 2019, Proceedings /: workshop and special sessions : 28th International Conference on Artificial Neural Networks, Munich, Germany, September 17-19, 2019, Proceedings. (2019) - Unknown
No abstract available